Serial Haemodynamic Change In Children With Acute Empyema - Virendra Kumar; G Unikrishnan; R Anand; R Rathore; G Sethy (Journal of Nepal Medical Association, 2004)
Empyema thoracis continues to remain a serious complication of Pneumonia in children. A number of studies are available on demographics, etiology and treatment of empyema but no useful information is available on hemodynamic changes occurring in response to acute empyema. Therefore we aimed to evaluate the serial haemodynamic changes in children with acute empyema and their correlation with severity and out come of the disease. Serial haemodynamic changes were studied prospectively in 25 children with acute empyema before and after the placement of chest tube and subsequently on day 1, 2, 3 and 10 of hospitalization. Twenty-five age and sex matched children served as their controls. Their age ranged from 8 months to 12 years (mean 4.2 years). Severity of empyema was graded as mild, moderate and severe in 11, 6 and 8 children respectively. Staphylococcus aureus was the commonest organism isolated in 11 children. At admission all the children were febrile (mean temp 39.4C) had tachycardia (mean HR136/mt) and tachypnea (mean RR 62/mt).While CVP was high (10.2? 4cm H2O), the systolic (102 ? 4mmHg) and mean arterial pressure(77? 3mmHg) was at lower side as compared to their controls.The mean changes observed after the chest tube placement were HR- 6/mt; RR - 4.44/ mt; SBP+5 mmHg; DBP +2.04mmHg; MAP +3mmHg and CVP-3.1cm H2o (p <.001). Children with severe disease had significantly higher CVP (15 ? 3.3cmH2o), low SBP (99 ? 3mmHg) and low serum Sodium (128 ? 5mEq/L) and Osmolality (278 ? 9 mOsm/L) compared to those with mild or moderate disease. (p<.05 for each factor).Seven children had features suggestive of syndrome of inappropriate ADH secretion. All this children belonged to severe category. It was concluded that hemodynamic compromise is a common occurrence in children with empyema. High CVP, low SBP, low serum Na+ and Osmolality correlate best with the severity of the disease.